Anti-Invariant Semi-Riemannian Submersions from Almost Para-Hermitian Manifolds. (10th November 2013) - Gündüzalp, Yılmaz
Abstract : We introduce anti-invariant semi-Riemannian submersions from almost para-Hermitian manifolds onto semi-Riemannian manifolds. We give an example, investigate the geometry of foliations which are arisen from the definition of a semi-Riemannian submersion, and check the harmonicity of such submersions. We also obtain curvature relations between the base manifold and the total manifold.